Changes in the Indonesian Constitution from the Beginning of Independence to the Reform Era - Annisa Yuana Putri; Nazwa Putroeu Utami; Miftahul Jannah (Jurnal Pengetahuan Sosial dan Sejarah, 2025)
This study aims to analyze the history of changes in Indonesia's constitution and identify the factors that led to the change. The research method uses qualitative analysis with historical and normative approaches. Data is obtained from library sources through scientific reference applications. The results of the study show that constitutional changes in Indonesia are driven by a variety of factors, including political instability, the push for democratization, and the need for a more inclusive legal system. The most significant constitutional reform occurred through the amendment of the 1945 Constitution in the Reform era which resulted in fundamental changes in the constitutional structure. The Indonesian Constitution is predicted to continue to undergo adjustments to remain relevant and responsive to the needs of the community.